2012
DOI: 10.1053/j.pcsu.2012.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Options for Prosthetic Pulmonary Valve Replacement

Abstract: This article reviews current data on various prostheses utilized for pulmonary valve replacement. Durability data is reviewed and risk factors for deterioration are examined. Finally, the choice of prosthesis should be tailored to the specific clinical scenario based on existing data regarding durability and risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 38 publications
0
6
0
1
Order By: Relevance
“…In this retrospective, observational, cohort study, the allocation of the 2 types of ePTFE conduit was decided only by the date of implantation except for the 4 months of transitional period, and the 2 groups were thought to be sufficiently comparable without any statistical corrections. Although the baseline characteristics of the patients in the 2 groups did not differ significantly, the proportion of patients who underwent the Ross operation was significantly greater in group N. Because the nonanatomic implantation of the conduit in RVOT reconstruction is known as an independent risk factor for conduit dysfunction, 16,17 this disproportion might work against group T. Except for this problem, all other data supported the statistical equivalency of the 2 groups; therefore, comparison between these 2 groups was thought to be appropriate.…”
Section: Discussionmentioning
confidence: 97%
“…In this retrospective, observational, cohort study, the allocation of the 2 types of ePTFE conduit was decided only by the date of implantation except for the 4 months of transitional period, and the 2 groups were thought to be sufficiently comparable without any statistical corrections. Although the baseline characteristics of the patients in the 2 groups did not differ significantly, the proportion of patients who underwent the Ross operation was significantly greater in group N. Because the nonanatomic implantation of the conduit in RVOT reconstruction is known as an independent risk factor for conduit dysfunction, 16,17 this disproportion might work against group T. Except for this problem, all other data supported the statistical equivalency of the 2 groups; therefore, comparison between these 2 groups was thought to be appropriate.…”
Section: Discussionmentioning
confidence: 97%
“…They are the valves of choice for children, adolescents, and adults. 20 All patients of PVR in our centre have bioprosthetic valves, porcine or pericardial valves. In our present study, matched cMRI data showed significant reduction in RV volumes but no changes in the RVEF.…”
Section: Discussionmentioning
confidence: 99%
“…They are the valves of choice for children, adolescents, and adults. 20 All patients of PVR in our centre have bioprosthetic valves, porcine or pericardial valves.…”
Section: Discussionmentioning
confidence: 99%
“…The homografts have been used in PVR and RVOT for several decades. Although they are capable of providing superior hemodynamic performance, free of anticoagulation and encouraging early-to mid-term outcomes, the discouraging long-term durability and limited availability constrained their clinical application (Emani, 2012). Bioprosthetic valves, which are usually constructed from the decellularized bovine or porcine pericardium, overcome the shortage of homograft.…”
Section: Introductionmentioning
confidence: 99%